Tamu : its roles as a medium of cultural identity preservation among Sabah ethnic in the era of information technology and industrial revolution 4.0 - Halina Sendera Mohd. Yakin; Andreas Totu; Siti Aidah Lokin; Suraya Sintang; Nadiawati Mahmood (Penerbit Universiti Kebangsaan Malaysia, 2022)
This paper aims to study the roles and challenges of Tamu as a medium of cultural identity preservation among Sabah ethnic groups in the era of industrial revolution 4.0 by focusing on the commercialisation of Kadazandusun’s traditional foods tuhau and bambangan. Thus, the objectives of this paper are to examine the existing and future functions of Tamu as well as to study the impact of industrial revolution 4.0 and the advancement of information technology on the role of Tamu in the commercialisation of traditional foods and preservation of cultural identity among Kadazandusun people. Both qualitative and quantitative data are gathered through participant observation, interviews, and surveys. The respondents and informants consist of Kadazandusun traditional foods retailers and consumers at various Tamus in Sabah. The findings show that the role of Tamu institution is still pertinent in commercialising traditional foods and preserving the cultural identity of the Kadazandusun people, particularly in the rural areas. At certain localities, such as those adjacent to the city and tourist attractions, Tamu still plays an essential role in commercialising traditional foods, even though some retailers have already utilised various types of social media to promote and expand their sales, specifically those who are operating as part-timers. Media and internet accessibility has been identified as contributing factors towards the change in the marketing approach. Other contributing factors include time and budget constraints and business location. Hence, Tamu is still relevant and significant in the context of commercialising traditional foods and preserving cultural identity among the Kadazandusun people in Sabah in the era of the digital revolution.